Relevansi Pasal 34 Ayat (1) UUD 1945 dan HR. Bukhari tentang Pemimpin (Deposisi: Jurnal Publikasi Ilmu Hukum, 2025)
This article aims to analyze the relevance of Article 34 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia which regulates state protection for the poor and neglected children, and its relation to the concept of leadership from an Islamic perspective. This study compares the legal provisions with the Hadith narrated by Bukhari which emphasizes the responsibility of leaders towards those they lead. The method used is qualitative analysis with a comparative approach to legal texts and related literature sources. The results of the study show that both Article 34 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia and the Hadith have similarities in emphasizing the importance of social responsibility towards underprivileged citizens, as well as describing the role of each individual as a leader in their social capacity.